2011
DOI: 10.1007/s13304-011-0119-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic mini-gastric bypass: short-term single-institute experience

Abstract: The elevated variety of procedures proposed for surgical treatment of obesity in the last few years suggests the necessity to find an ideal operation. Laparoscopic mini-gastric bypass (LMGB) was developed to obtain better results with lesser morbidity and mortality. LMGB was introduced by Rutledge, in 1997, and it consists of a long lesser-curvature tube with a terminolateral gastroenterostomy 180 cm distal to the Treitz ligament. From July 1995 to May 2011 we have performed 552 bariatric operations, among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…The metabolic effects are summarized in another chapter in the present issue of the article, but it is a popular research subject studied by various researchers. [7][8][9][10][11][12][13][14][15][16] All data are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The metabolic effects are summarized in another chapter in the present issue of the article, but it is a popular research subject studied by various researchers. [7][8][9][10][11][12][13][14][15][16] All data are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Our results have also indicated an excess body weight loss rate of 68.7% and 83.4% in 6 months and 1 year, respectively (See Table 2 for details), which is comparable to the data shown in the literature by high volume centers. [2][3][4][5][6][7][11][12][13][14][15][16] However, our results seem better since it is a single center study and a single surgeon performed the surgeries in less than two years.…”
Section: Excess Body Weight Loss Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…T2DM remission rates were mostly more than 84% [18,[20][21][22][23][26][27][28][29] Table 2 details the summary of complications in the same studies. 9 studies reported 0% mortality in their series.…”
Section: Efficacy-weight Loss and Resolution Of T2dmmentioning
confidence: 98%
“…and pre-and post-operative clinic, inspecting his substantial follow-up. The MGB has since increased throughout the world [3][4][5][6][7][8][9][10][11][12][13][14]. With the decrease in gastric banding, the MGB in 2015 became the third most common bariatric operation internationally [15].…”
Section: Introductionmentioning
confidence: 99%